A pragmatic analysis of the implicatures in the UK Prime Minister Keir Starmer’s speech recognizing the State of Palestine - Maysam Mohammad Rjoub; Dr. Mahmood Eshreteh (Yayasan Mitra Persada Nusantara, 2026)
This research examines the pragmatic analysis of the UK Prime Minister Keir Starmer's speech announcing the official recognition of the State of Palestine on September 21, 2025. Using Grice's conversational maxims quality, quantity, manner and relation, the speech is analyzed and its deliberate violations are exposed, with a focus on how these violations that generate implicit meanings that reflect the UK's diplomatic position. By applying a qualitative descriptive analytical framework, the research explores deliberate ambiguities, strategic omissions, and indirect language that serve the UK's international and domestic political objectives. The findings reveal that the discourse employs pragmatic strategies to balance support for Israel's security with recognition of a Palestinian state, justifying political decisions while appeasing public opinion. The analysis highlights the role of language as a tool for persuasion, negotiation, and justification in sensitive political issues, contributing to a deeper understanding of how political discourse shapes international relations.